275 nm Deep Ultraviolet AlGaN-Based Micro-LED Arrays for Ultraviolet Communication - Liang Guo (IEEE, 2022)
In this work, we fabricated and characterized 4 × 4 parallel flip-chip AlGaN-based micro-LED arrays with varied mesa diameters of 120 µm, 100 µm, 80 µm, and 60 µm. The reported micro-LED arrays have a maximum bandwidth of 380 MHz and a peak wavelength of ∼275 nm. It is found that the electrical and optical characteristics of AlGaN-based micro-LED arrays show strong size dependence for ultraviolet communication (UVC). The differential resistance increases from 28.8 Ω to 112 Ω, the external quantum efficiency (EQE) is increased by ∼30%, and the bandwidth doubles as the diameter of individual micro-LED decreases from 120 µm to 60 µm. Our research proves that tailoring the mesa size of parallel flip-chip AlGaN-based micro-LED arrays can further enhance its bandwidth and promote its application in UVC.